Implementasi Komunikasi Multi-Hop Menggunakan Metode Controlled Flooding Pada Wireless Sensor Network Berbasis LoRa - Zeddin Arief; Primantara Hari Trisnawan; Achmad Basuki (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Wireless sensor network (WSN) is a wireless network that requires there are at least two interconnected nodes to communicate using wireless communication modules. One of the communication modules that has low power consumption and a considerable distance is the Long Range (LoRa). However, the limitations of LoRa that only uses single wireless hop communication creates problems when implementing LoRa networks to reach dark spots or areas that are difficult to reach by the network. Therefore, this research applies multi-hop communication using controlled flooding method. The application of controlled flooding method uses several mechanisms to resolve problems in the flooding method in general. There are mechanism of preventing infinite loop transmission, random delay mechanism, and packet retransmission mechanism. After testing, it was found that the infinite loop transmission prevention mechanism was successful in resolving the same packet forwarding over and over again. In addition, the packet retransmission mechanism for resolving if a packet lost is also successful. Then the performance test results show that the random delay mechanism is able to cut the percentage of packet loss. The test results show when using a random delay mechanism the packet loss results are 18%. Whereas when without using the random delay mechanism the packet loss results are 54%.